2004
DOI: 10.1021/jo049681x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic/Experimental Electron Density Characterizations and Reactions with Nucleophiles of β-Enaminonitriles Possessing a Pyrrolobenzazepine Core

Abstract: In connection with a total synthesis of cephalotaxine (1a), we have examined the addition of various nucleophilic reagents to [ABC] subunits 2 and 7 possessing a pyrrolobenzazepine core. In fact, this reaction implicates invariably the carbonyl group of 2. Regarding the reaction of 7 with nucleophiles, the most striking aspect is the complete lack of reactivity of the enaminonitrile moiety. For instance, the condensation of 7 with methylmagnesium bromide involves exclusively the cleavage of the dioxole ring, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…113 During this work, the unexpected lack of reactivity of the enaminonitrile moiety of products was studied by crystallographic and experimental electron density characterization. 114 It showed marked reactivity of the amide carbonyl group due to the weakness of the amide resonance resulting from pronounced delocalization of the nitrogen lone pair over the enaminonitrile part. Beall and Padwa also developed an approach to the cephalotaxine ABC ring skeleton using an ammonium ylide/Stevens [1,2]-rearrangement, thus forming the pyrrolobenzazepine core from an isoquinoline bearing a N-alkyldiazoketone.…”
Section: Biosynthetic Origin Of Cephalotaxus Alkaloidsmentioning
confidence: 99%
“…113 During this work, the unexpected lack of reactivity of the enaminonitrile moiety of products was studied by crystallographic and experimental electron density characterization. 114 It showed marked reactivity of the amide carbonyl group due to the weakness of the amide resonance resulting from pronounced delocalization of the nitrogen lone pair over the enaminonitrile part. Beall and Padwa also developed an approach to the cephalotaxine ABC ring skeleton using an ammonium ylide/Stevens [1,2]-rearrangement, thus forming the pyrrolobenzazepine core from an isoquinoline bearing a N-alkyldiazoketone.…”
Section: Biosynthetic Origin Of Cephalotaxus Alkaloidsmentioning
confidence: 99%
“…It has been demonstrated that accurate electron density can give pertinent informations on the interactions between potent drug and their biological targets. Experimental X-ray determination of the accurate electron density in compounds containing transition metals has grown as a major area in the past few years. Most of the progress is due to the recent availability of fast devices like area detectors which provide full and very accurate data sets in short times even for crystals with large unit-cells.…”
Section: Introductionmentioning
confidence: 99%
“…After having explored ABC / ABCD synthetic strategies, 116,117 in 2005, Dumas and d'Angelo et al reported a novel enantioselective synthesis of the azaspiro unit (À)-304 containing CD rings described by Royer 132 based on an asymmetric Michael reaction involving a chiral enamine prepared from cheap and recyclable enantiopure (R)-1-phenylethylamine 309 (Scheme 30). 135 As a consequence of stereogenic control of the quaternary carbon center in the resulting (R)-ketodiester 311, the two asymmetric centers C3 and C4 of CET (À)-(1) were formed with their natural ACs.…”
Section: Dumas and D'angelo's Formal Synthesis (2005)mentioning
confidence: 99%